100 highlights of the collections of the Oriental Institute Museum - University of Chicago Oriental Institute Museum; Evans, Jean M. 1972-; Green, Jack ca. 20./21. Jh.; Teeter, Emily 1953- (Chicago Oriental Institute Museum, The University of Chicago, 2019)
"In honor of the Oriental Institute's centennial celebration, this special edition guide to 100 select highlights of the collections of the Oriental Institute Museum at the University of Chicago presents objects from ancient Mesopotamia, Syro-Anatolia, the Levant, Egypt, Nubia, and Persia. The guide features a history of the collections, new photography, provenance information, and a brief description of each object"--
"OI centennial special edition publication."
Archivierung/Langzeitarchivierung gewährleistet
Keywords: University of Chicago -- Oriental Institute -- Museum -- Catalogs; Art -- Illinois -- Chicago -- Catalogs; Art, Ancient -- Middle East -- Catalogs; Middle East -- Antiquities -- Catalogs